Antibiotic-Resistant Bacteria Are Major Threats of Otitis Media in Wollo Area, Northeastern Ethiopia: A Ten-Year Retrospective Analysis - Ayele Argaw-Denboba; Asrat Agalu Abejew; Alemayehu Gashaw Mekonnen (International Journal of Microbiology)
Antibiotic resistance is an increasingly serious threat to human health that needs an urgent action. The aim of this study was to determine the prevalence and antibiotic susceptibility profiles of bacteria isolated from patient ear discharges suspected of otitis media. A retrospective analysis was performed using culture and antibiotic susceptibility test results of 1225 patients who visited Dessie Regional Health Research Laboratory from 2001 to 2011. Results showed a strong association (P<0.001) between age and the risk of acquiring middle ear infection. The predominant bacterial isolates were Proteus spp. (28.8%), Staphylococcus aureus (23.7%), and Pseudomonas spp. (17.2%). Most of the isolated bacteria showed high resistance to ampicillin (88.5%), ceftriaxone (84.5%), amoxicillin (81.9%), and tetracycline (74.5%). About 72.5% of Proteus spp. and 62.2% of Pseudomonas spp. have developed resistance to one and more antibiotics used to treat them. This retrospective study also revealed the overall antibiotic resistance rate of bacterial isolates was increased nearly twofold (P=0.001) over the last decade. Relatively, ciprofloxacin and gentamicin were the most effective antibiotics against all the isolates. In conclusion, antibiotic-resistant bacteria are alarmingly increasing in Wollo area, northeastern Ethiopia, and becoming a major public health problem in the management of patients with middle ear infection.